STUDENTS’ ANXIETY IN SPEAKING ENGLISH AT SECOND SEMESTER OF ENGLISH STUDY PROGRAM AT UNIVERSITY OF PASIR PENGARAIAN - Rahmad Kurniadi; Evi Kasyulita (English Study Program University of Pasir Pengaraian, 2019)
Anxiety is uncomfortable feeling that someone feels in facing any situation. Anxiety is common problem in speaking especially to learners.The purpose of the research was to find out the factors and the types of students’ anxiety in speaking at second semester students of English study program at University of Pasir Pengaraian. This research was design a descriptive qualitative research and instrument that the researcher used in collecting the data is questionnaire. The sample of the research were 15students. The finding result of the research showed, there were 14 students classified into state anxiety, and 1 students classified into trait anxiety. So the most of second semester students were classified into state anxiety.This result was taken from open-ended questions.